Thiolutin is a zinc chelator that inhibits the Rpn11 and other JAMM metalloproteases - Lauinger, Linda; Shostak, Anton; Cemel, Ibrahim; Ha, Nati; Stankovic-Valentin, Nicolas; Melchior, Frauke; Brunner, Michael; Diernfellner, Axel (Nature chemical biology, 2017)
Thiolutin is a disulfide-containing antibiotic and anti-angiogenic compound produced by Streptomyces. Its biological targets are not known. We show that reduced thiolutin is a zinc chelator that inhibits the JAB1/MPN/Mov34 (JAMM) domain-containing metalloprotease Rpn11, a deubiquitinating enzyme of the 19S proteasome. Thiolutin also inhibits the JAMM metalloproteases Csn5, the deneddylase of the COP9 signalosome; AMSH, which regulates ubiquitin-dependent sorting of cell-surface receptors; and BRCC36, a K63-specific deubiquitinase of the BRCC36-containing isopeptidase complex and the BRCA1-BRCA2-containing complex. We provide evidence that other dithiolopyrrolones also function as inhibitors of JAMM metalloproteases.